Combined wave-current scale model testing at FloWave - Noble, Donald Ross (Ocean Engineering, 2018)
As part of a global drive to produce renewable electricity, devices are being designed to harness energy from the waves and tidal currents. Physical scale model testing is an important part of the development process for this and other technologies. The FloWave Ocean Energy Research Facility at The University of Edinburgh is designed to conduct these tests. Here it is possible to produce multi-directional waves combined with currents in the circular tank, re-creating the complexity of the ocean. The research was driven by commercial requirements of the facility, aiming to highlight what can be learnt from testing at scale with complex conditions in a controlled environment. To enable this, it was first necessary to extend the characterisation of this new facility. Wave generation and reflections were assessed in a previous project. In this work, flow measurements taken throughout the test volume of the tank, allowed spatial and temporal variations in the currents to be determined. Waves and currents interact in a complex manner, compounded by the method of reproducing them in a tank. The influence of currents on waves in the basin was assessed. This included cases with an oblique angle between them, on which little has been published. The other part of the project addressed issues to be considered when testing in a combined wave-current basin such as FloWave. • At many sites of interest for offshore renewable energy, waves are influenced by water depth. Implications of not scaling depth consistently were considered, and design diagrams produced to facilitate understanding and quantification of potential errors. • At FloWave, waves are generated in still water around the outside of the tank. A process was therefore developed and verified to produce the desired combined conditions in the central test area following their interaction with the current. • There is a wealth of published guidance on tank testing, for ships, offshore structures, and more recently renewable energy. This has been reviewed and suggestions ...